Some features of the application of the norms of international private law to civil-legal relations to regulate obligations due to harm (delicate liabilities) (Eurasian Research Bulletin, 2023)
The article discusses some features of the legal regulation of obligations as a result of causing harm (tort obligations) in international private law of the Republic of Uzbekistan based on the provisions of the Civil Code of the Republic of Uzbekistan, the articles of the Model Civil Code for the member states of the Commonwealth of Independent States, the provisions of the Agreement on Dispute Resolution, related to the implementation of economic activities (Kiev, March 20, 1992) and the Convention on Legal Assistance and Legal Relations in civil, family and criminal matters (Minsk, January 20, 1993). The article formulates proposals for the improvement of the civil legislation of the Republic of Uzbekistan in the field of regulation of obligations as a result of harm caused by a foreign element.